PENGARUH KINERJA PENGURUS KOPERASI TERHADAP PARTISIPASI ANGGOTA KOPERASI SRI MERSING DI SMK N 1 SELATPANJANG - Sari, Novita Puspa; Gusnardi, Gusnardi; Ngadlan, Ngadlan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractThis study aims to determine the effect on the performance of the union board member participation in Sri Mersing Union in SMK N 1 Selatpanjang. This research was conducted in the savings and loan Sri Mersing UnionSelatpanjang from March to Mei 2014. The research method used is descriptive quantitative method. The population is all members of the Sri Mersing Union. 61 respondents were selected as a sample of union members who are not serving as manager and supervisors. Data collection instrument used was a questionnaire with Likert scale for the dependent variables : participation of members (Y) ; independent variables : the performance of the board (X). Data analysis techniques used are statistical techniques with simple linear regression. From the results, it can be concluded that : (1) the performance of the board affect the participation of members of the Sri Mersing Union; (2) the effect of the board's performance against the participation of members of the Sri Mersing Union Selatpanjang amounted to 49.4 %                                  Key words : union, performance, participation